The enhanced ferroelectric properties of flexible Hf0.85Ce0.15O2 thin films based on in situ stress regulation - Jinglin Pang; Tianpeng Duan; Min Liao; Limei Jiang; Yichun Zhou; Qiong Yang; Jiajia Liao; Jie Jiang (npj Flexible Electronics)
Abstract As the core component of ferroelectric memories, HfO2-based ferroelectric thin films play a crucial role in achieving their excellent storage performance. Here, we improved the ferroelectric properties and domain switching properties through in situ stress loading during annealing. The thin films are annealed under different bending states by applying different stress actions, and it is observed that, within a certain range of stress bending, the optimization of the ferroelectric properties of the annealed thin films can reach an extreme value. Specifically, under the influence of a small electric field, the 2P r values of thin films annealed at +10 and −10 mm increased by 87.1% and 71.1%, respectively, compared with the unbent films. Additionally, these thin films exhibit extremely high domain wall mobility and excellent domain switching capabilities. Once the ferroelectric phase is formed through in situ stress modulation, it remains stable even under multiple service environments.